Diurnal Variation in PAI-1 Activity Predominantly Confined to the 4G-allele of the PAI-1 Gene - Hoekstra, Tiny; Geleijnse, Johanna M.; Schouten, Evert G.; Kluft, Cornelis (Thrombosis and Haemostasis, 2002)
We examined the diurnal pattern in Plasminogen Activator Inhibitor-type 1 (PAI-1) activity and Plasminogen activator (t-PA) in relation to the 4G/5G-polymorphism in the promoter of the PAI-1 gene. The analyses were performed in the Arnhem Elderly Study, a populationbased study of 598 elderly. A single blood sample was drawn and the time of blood sampling was recorded (between 8 a. m. and 5.30 p. m.). Plasma PAI-1 activity was strongly associated with time of blood sampling, showing the highest values in the early morning. The diurnal pattern was clearly present in the 4G/4G (n = 184) and 4G/5G (n = 275) genotypes, but not in the 5G/5G-genotype (n = 139). T-PA antigen showed a weak diurnal variation, which did not differ across the variants of the 4G/5G-polymorphism. Our findings raise the hypothesis that 5G-homozygotic persons may be relatively protected from diurnal variation in the occurrence of coronary events.
Keywords: Fibrinolysis; diurnal variation; PAI-1; t-PA; 4G/5G-polymorphism